Pengaruh Penggunaan Chatbot terhadap Kinerja Akademik Mahasiswa FKIP dan Non FKIP dengan Self Efficacy, Keadilan dan Etika, Kreativitas, dan Keinginan untuk Belajar sebagai Variabel Mediasi - Stevany Bella Dianita Kusuma; Muhammad Sabandi (FKIP Unswagati, 2025)
Student performance is widely recognized as a critical factor in higher education and must be improved in a strategic, structured, and sustainable manner, in alignment with students’ competencies and professional development. This study employs quantitative research design with descriptive analysis. A total of 400 university students in Surakarta participated in the study, selected using purposive sampling. Data was collected through an online questionnaire administered via Google Forms. The validity of the instrument was assessed using convergent and discriminant validity, while reliability was evaluated through cronbach’s alpha and composite reliability. Data analysis was conducted using descriptive statistics, and hypothesis testing was performed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, using SmartPLS 4.0 software. The findings reveal that: (1) the effect of penggunaan chatbot has a significant positive effect on students’ academic performance; (2) self-efficacy, fairness and ethics, creativity, and the desire to learn significantly mediate between penggunaan chatbot and academic performance; (3) trust significant moderator between self-efficacy, fairness and ethics, and creativity with academic performance; and (4) penggunaan chatbot on academic performance mediated by self-efficacy, fairness and ethics, creativity, the desire to learn, and trust is more pronounced among non- teacher education programs students than teacher education programs students. Keywords: chatbot, academic performance, self-efficacy, fairness and ethics, creativity